Direct conversion of cheese whey to polymalic acid by mixed culture of Aureobasidium pullulans and permeabilized Kluyveromyces marxianus. (October 2021) - Xia, Jun; He, Jianlong; Xu, Jiaxing; Liu, Xiaoyan; Qiu, Zhongyang; Xu, Ning; Su, Long
Graphical abstract: Highlights: Cheese whey was directly used for polymalic acid (PMA) fermentation. Ethanol treated K. marxianus were compatible with A. pullulans for PMA production. Obtained high PMA titer 97.3 g/L, yield 0.56 g/g and productivity 0.51 g/(L·h). The reusability of permeabilized K. marxianus cells was poor. Abstract: Cheese whey is an abundant and low-cost feedstock with lactose as its main component, but the inability to metabolize lactose prevents Aureobasidium pullulans from using cheese whey directly. In this study, Kluyveromyces marxianus was permeabilized to obtain nonviable but biocatalytic cells for lactose hydrolysis, and the mixed culture of A. pullulans and permeabilized K. marxianus was conducted for polymalic acid (PMA) production from cheese whey. In the mixed culture, PMA titer varied directly to β -galactosidase activity of K. marxianus, but inversely to cell viability of K. marxianus, and ethanol permeabilized K. marxianus was the most compatible with A. pullulans for PMA production. 37.8 g/L PMA was produced in batch fermentation, and PMA titer was increased to 97.3 g/L in fed-batch fermentation, with a productivity of 0.51 g/(L·h) and a yield of 0.56 g/g. This study paved an economical and environmentally friendly way for PMA production from cheese whey.